Student nurses’ knowledge of guidelines for preventing central venous catheter-associated infections - Al Qadire, Mohammad; Tawalbeh, Loai; Suliman, Mohammad (International Journal of Advanced Nursing Studies, 2017)
Background: Despite the advantages of Central venous catheters (CVC), patients are at high risk of infection (local and systematic) that could be lethal. Lack of knowledge of the available guidelines for the prevention of CVC-associated infection may increase the rate of CVC-associated infections.Objective: The purpose of the study is to evaluate student nurses’ knowledge of the guidelines for preventing CVC-associated infection.Methods: A descriptive cross-sectional survey was used. This study involved 267 student nurses from four government universities. They were in their second-, third- or fourth-year of study.Results: Most of the students were female (72.3%) with a mean age of 21.2 (SD 2.5). The mean total score of students’ knowledge was very low at 1.6 (SD 1.5) out of 10, the maximum score, and ranged from 0 to 7. Students who reported having received adequate theoretical and clinical education about CVC had higher mean total knowledge scores than those who had not.Conclusions: The results showed that Jordanian student nurses have insufficient knowledge about the prevention of CVC-associated infection. In order to improve their knowledge, an evidence-based teaching approach is required in the theoretical classes. This should be combined with the best clinical training through the use of simulation techniques.